FINANCIAL PERFORMANCE TO DETERMINE FINANCIAL DISTRESS CONDITIONS - Yustina Indi Savery; Haninun Haninun; Riswan Riswan (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The aim of this study is to examine the relationship between financial performance and the prediction of financial distress in a mining sector company listed on the Indonesia Stock Exchange from 2018 to 2022. A quantitative research method was employed for this study. The study focused on three independent variables, namely profitability, liquidity, and leverage, which were used to measure financial performance. The dependent variable, financial distress, was measured using the Altman Z-score model. A purposive sampling method was used to select 90 samples for this research, including 18 companies in the mining sector listed on the Indonesia Stock Exchange from 2018 to 2022. The data was analyzed using SPSS 17, with logistic regression as the chosen analysis method. The findings of this study indicate that profitability, as measured by ROA, and liquidity, as measured by CR, have a negative and significant impact on financial distress. Additionally, leverage, as proxied by DAR, has a positive and significant effect on financial distress.